Strategi Nilai-Nilai Kebangsaan Berbasis UUD 1945 Pasa Diversifikasi Ekonomi Untuk Mengurangi Ketergantungan Pada Sektor Migas - Edy Soesanto; Muhammad Al Hafiz Mattauch (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
In an effort to reduce economic dependence on the oil and gas sector, the country needs to diversify through various policies such as infrastructure investment, fiscal policies that support non-oil and gas sectors, education and training for skilled labor, research and innovation, export promotion, international partnerships, wise management of natural resources, support for SMEs, public-private partnerships, and continuous evaluation. Economic diversification is considered essential to achieve sustainable economic growth and to be resilient to fluctuations in world oil prices. Oil and gas trade, non-oil and gas exports, and foreign investment play a crucial role in Indonesia's economy. Economic diversification and the development of alternative energy sources are key to mitigating the economic risks associated with oil price fluctuations. Although challenges and constraints exist, the long-term benefits of economic diversification are vital for economic stability and sustainable growth. Oil and gas trade has a significant impact on Indonesia's economy, contributing significantly to state revenues but is also vulnerable to fluctuations in oil and gas prices in the global market. Therefore, economic diversification is an important strategy to reduce the economic risks associated with dependence on the oil and gas sector. This study aims to provide a deeper understanding of the dynamics of oil and gas trade and its impact on the Indonesian economy.